2010
DOI: 10.2337/db09-1560
|View full text |Cite
|
Sign up to set email alerts
|

Local Expression of Indoleamine 2,3 Dioxygenase in Syngeneic Fibroblasts Significantly Prolongs Survival of an Engineered Three-Dimensional Islet Allograft

Abstract: OBJECTIVEThe requirement of systemic immunosuppression after islet transplantation is of significant concern and a major drawback to clinical islet transplantation. Here, we introduce a novel composite three-dimensional islet graft equipped with a local immunosuppressive system that prevents islet allograft rejection without systemic antirejection agents. In this composite graft, expression of indoleamine 2,3 dioxygenase (IDO), a tryptophan-degrading enzyme, in syngeneic fibroblasts provides a low-tryptophan m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 50 publications
3
52
0
Order By: Relevance
“…Our research group conducted a series of novel studies showing the potential use of three-dimensional islet grafts equipped with IDO-expressing dermal fibroblasts to prevent islet allograft rejection without systemic immunosuppressive agents. We showed that IDO genetically modified islets transplanted into mouse kidney capsules survive longer than those islets transplanted without IDO expressing fibroblasts (Jalili et al 2010). This prolongation was due to the expression of IDO preventing T cell proliferation and infiltration into transplanted allogeneic islets (Jalili et al 2010).…”
Section: Role Of Ido Expression In Allogeneic Islet Transplantationmentioning
confidence: 91%
See 4 more Smart Citations
“…Our research group conducted a series of novel studies showing the potential use of three-dimensional islet grafts equipped with IDO-expressing dermal fibroblasts to prevent islet allograft rejection without systemic immunosuppressive agents. We showed that IDO genetically modified islets transplanted into mouse kidney capsules survive longer than those islets transplanted without IDO expressing fibroblasts (Jalili et al 2010). This prolongation was due to the expression of IDO preventing T cell proliferation and infiltration into transplanted allogeneic islets (Jalili et al 2010).…”
Section: Role Of Ido Expression In Allogeneic Islet Transplantationmentioning
confidence: 91%
“…We showed that IDO genetically modified islets transplanted into mouse kidney capsules survive longer than those islets transplanted without IDO expressing fibroblasts (Jalili et al 2010). This prolongation was due to the expression of IDO preventing T cell proliferation and infiltration into transplanted allogeneic islets (Jalili et al 2010).…”
Section: Role Of Ido Expression In Allogeneic Islet Transplantationmentioning
confidence: 91%
See 3 more Smart Citations